Schleichera oleosa L oil as feedstock for biodiesel production - Silitonga A.S.; Masjuki H.H.; Mahlia T.M.I.; Ong H.C.; Kusumo F.; Aditiya H.B.; Ghazali N.N.N. (Elsevier Ltd, 2023)
Alternative fuels; Biodiesel; Catalysts; Diesel engines; Esterification; Esters; Feedstocks; Gasoline; Methanol; Oil shale; Optimization; Transesterification; Biodiesel production; Catalyst concentration; Non-edible oil; Optimum conditions; Oxidative stability; Reaction temperature; Schleichera oleosa; Two-step transesterification; Analysis of variance (ANOVA)